A prática da fonética forense no Brasil: proposta de um modelo de investigação - Mata, Ingrid da (Universidade Federal de São Carlos, 2024)
Forensic Phonetics is a specialized field within forensic sciences that focuses on the study and analysis of human voice with the aim of using this information as evidence in criminal investigations (HUGHES, 2014). In Brazil, Forensic Phonetics is still a relatively new area but has been growing exponentially in the past few years. Given the heterogeneity of practices and methodologies in the field, it becomes important to map the Brazilian context — a vast country with a variety of cultures, distributed across 27 states, exhibiting significant geographical, cultural, and legal diversity, which is not taken into consideration in international studies in the field. Therefore, the objective of this work is to propose an investigation method to assist in mapping the current practices and methodologies in the field of Forensic Phonetics in Brazil and contribute to the development of the area.
The practice of forensic phonetics in Brasil: a proposal for an investigation model
Keywords: Fonética forense; Criminalística; Tarefas de fonética forense; Métodos em fonética forense; Comparação de locutores; Forensic phonetics; Forensic science; Forensic phonetics tasks; Forensic phonetics methods; Speaker comparison; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA